2005
DOI: 10.1093/jn/135.9.2119
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene Inhibits Cell Migration and Invasion and Upregulates Nm23-H1 in a Highly Invasive Hepatocarcinoma, SK-Hep-1 Cells

Abstract: The carotenoid lycopene has been associated with decreased risks of several types of cancer, such as prostate cancer and hepatoma. Tumor metastasis is the most important cause of cancer death. Although lycopene was shown to inhibit metastasis, the mechanism underlying this action is not well understood. Here, we tested the possibility that lycopene may inhibit cancer cell metastasis by upregulating the expression of nm23-H1, a metastasis suppressor gene, in SK-Hep-1 cells, a highly invasive hepatoma cell line,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 39 publications
6
52
0
1
Order By: Relevance
“…This parabolic trend may be due to autooxidation of the compounds at concentrations 10 lM, as reported in a similar study with lycopene. 18 Further, in a bleomycin assay, hydroxytyrosol has been reported to have pro-oxidant effects at a concentration of 0.01% (w/v), 19 which may account for the parabolic dose respond effect in our invasion assay.…”
Section: Discussionmentioning
confidence: 84%
“…This parabolic trend may be due to autooxidation of the compounds at concentrations 10 lM, as reported in a similar study with lycopene. 18 Further, in a bleomycin assay, hydroxytyrosol has been reported to have pro-oxidant effects at a concentration of 0.01% (w/v), 19 which may account for the parabolic dose respond effect in our invasion assay.…”
Section: Discussionmentioning
confidence: 84%
“…Park et al [120] demonstrated the inhibitory effect exerted by lycopene in Hep3B cells through mechanisms involving cell cycle arrest in the G0/G1 phase and DNA damage. This tetraterpenoid also effectively displayed antimigration and anti-invasive properties against highly invasive SK-Hep-1 cells which were associated with the increase of the metastasis suppressor gene, nm23-H1 [115] . The study by Hwang and Lee [121] concluded with similar results displaying lycopene's inhibitory effects on adhesion, invasion and migration of SK-Hep-1 cells.…”
Section: Tetraterpenesmentioning
confidence: 97%
“…Antioxidant mechanisms 2.5-20 μmol/L Kozuki et al [114] Inhibited the migration of SK-Hep-1 cells 1-20 μmol/L Huang et al [115] Delayed the proliferation and improved the differentiation of oval cells obtained from neoplastic liver ↑albumin; ↑fibrinogen; ↑ hapatoglobin 5 μmol/L Wójcik et al [116] Exerted genotoxic and cytotoxic effects in HepG2 cells ↑apoptosis; ↑necrosis; ↑TBARS 4-8 μmol/L Yurtcu et al [117] Fucoxanthin Inhibited the growth of HepG2 cells ⊥G0/G1; ↓cyclin D1, D3; ↓cdk4; ↓pRb 10-50 μmol/L Das et al [118] Exhibited antiproliferative effect against SK-Hep-1 cells ↑apoptosis; ⊥G0-G1; ↑GJIC; ↑Cx43; ↑Cx32; ↓pJNK; ↓pERK; ↑[Ca] [119] Lycopene Suppressed the invasive property of AH109A cells [114] Induced an inhibitory effect on the growth of Hep3b cells [120] Displayed antimigration and anti-invasive activity in SK-Hep-1 cells [115] Inhibited adhesion, invasion and migration of SK-Hep-1 cells ↓MMP-9, -2 0.1-50 μmol/L Hwang et al [121] Inhibited SK-Hep-1 cell invasion ↓MMP-9; ↓NF-κB; ↑IκBα; ↓Sp1; ↓IGF-1R; ↓ROS 1-10 μmol/L Huang et al [122] Sesquiterpenes α-Bisabolbol Induced cytoxicity in HepG2 cells ↑apoptosis; ↑caspase-8, -9; ↑cyt. c; ↑Bax; ↑Bak; ↓Bcl-2; ↑p53; ↑NF-κB; ↑Fas [123] Dehydrocostuslactone…”
Section: Lupeolmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that increased cell migration does not always imply increased invasiveness (21,41). Hence, we elected to examine the role of tyrosinephosphorylated villin and PLC-␥ 1 in transmembrane migration of cells through Matrigel.…”
Section: Plc-␥ 1 Is Required For Villin-induced Increase In Cell Migrmentioning
confidence: 99%